Hypertension in Pregnant Females Promotes Thrombocytopenia - Aasma Naz, Amanullah Bhutto, Kiran Memon, Ghulam Fatima, Shabnam, Yasmeen Rasheed Bhutto, Aamir Ramzan, Kiran Aamir, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine how often pregnant hypertensive women get thrombocytopenia during the pregnancy. Study Design: Retrospective study Place and Duration: People university of Medical and Health Sciences for Women Nawabshah. January 2022 to December 2022. Methods: Total 63 pregnant females were presented. All the presented females had pregnancy induced hypertension with age group 18-46 years. All cases included platelet estimate, and thrombocytopenia was diagnosed in individuals with a reported platelet count of less than 1,50,000/cumm. All data were analyzed with SPSS 24.0. Results: Pregnant females had mean age 28.6±4.35 years and had mean BMI 26.4±3.29 kg/m2. Frequency of primigravida was 27 (42.9%) and 36 (57.1%) cases were multi-gravida. Majority of the patients 55 (87.3%) had blood pressure 140-160/90-110 mmHg and 8 (12.7%) cases had Bp > 160/110 mmHg. Frequency of thrombocytopenia was found in 17 (26.98%) cases. Among 17 cases of thrombocytopenia mild PIH was found in 3 cases, moderate in 5 cases and 8 cases had severe PIH. Conclusion: In particular, in third-trimester hypertensive pregnant women, gestational thrombocytopenia (GT) is recognized as a primary cause of thrombocytopenia. For those women, careful monitoring both during and after pregnancy is advised. Keywords: Thrombocytopenia, Gestational hypertension, Pregnancy